PENGARUH PERENDAMAN AIR DINGIN TERHADAP PERKECAMABAHAN BENIH CEMARA LAUT (Casuarina equisetifolia L.) - Yopa Dwi Mutia; Afri Rona Diyanti (Jurnal Embrio, 2022)
The trouble confronted to satisfy the wishes of Casuarina equisetifolia seeds is the low germination of Casuarina equisetifolia seeds resulting from dormancy. One of the natural approaches that may be used to increase the velocity of water getting into the seeds, especially seeds with a totally hard outer shell structure is soaking the seeds in cold water that's notion to interrupt the lignin bonds within the seed coat. The reason for this look at changed into to choose the ideal remedy as to a method of breaking Casuarina equisetifolia seed dormancy to improve seed viability and vigor. This test used a completely randomized design (CRD) with three treatments and eight replications, performed on the Laboratory of the Faculty of Agriculture, Tamansiswa Padang University, from July to August 2021. This test consisted of soaking the seeds in cold water. The observational information has been analyzed the use of the F check on the 5% level. If it is significantly different, it is endured using the honest significant difference (HSD) take a look at on the 5% level. The results of the look at gave a significant effect on the variables of germination, dead seeds, the first day of counting, and maximum growth potential.